The policy we want: an economic policy for informal traders in South Africa - Ngidi, Siphelele; Francis, David (University of the Witwatersrand, Johannesburg, 2025)
In 2024, SCIS, in partnership with WIEGO (Women in Informal Employment: Globalising and Organising), embarked on a research and policy project to develop an economic policy for informal traders in South Africa. The project gathered insights from individuals actively working in the sector, offering valuable perspectives for policymakers and stakeholders seeking to improve the conditions of informal traders and strengthen the informal trading economy. Based on these findings, we identified actionable policy recommendations to help create a more conducive environment for informal trading. The results are presented in a policy brief structured around eight key pillars, titled “The Economic Policy We Want.”
This policy brief was submitted to the Faculty of Commerce, Law and Management, Southern Centre for Inequality Studies (SCIS), at the University of the Witwatersrand, Johannesburg, 2025
Keywords: Informal traders; Informal sector; South Africa; Policy; Southern Centre for Inequality Studies (SCIS); SDG-8: Decent work and economic growth